Implementation of multicultural education in Islamic education management in As-Salam Bandung High School - Junaedi, Dedi; Fathuloh, Fathuloh; Zumailah, Elly; Sa’diah, Titin; Sahliah, Sahliah; Mahmud, Mahmud (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2024)
Indonesia is a country that has diversity, culture, ethnicity, language and religion, the impact of differences in society often causes problems and hostility and even bloodshed due to heterogeneous understanding. In fact, if differences are combined well, it will produce diversity and awareness that this is all a gift from God which has given the potential to become a pluralistic society in terms of cultural dimensions which will bring a more mature civilization towards a just, harmonious, advanced and prosperous nation. The aim of this research is to implement multicultural education at As-Salam High School in Islamic education management education. The method used is a qualitative method with a library study approach which is then analyzed. The results of this research, Multicultural Education is a concept that must be implemented in everyday life, especially applied in schools so that students have a paradigm/mainsentor a mindset of accepting differences and mutual respect, tolerance, diversity, equality of rights and obligations with the Pancasila philosophy with a Tunggal Ika diversity frame, even though we are different, we are one Indonesian unit. Differences due to the essence of life, everything does not have to be the same, but how can these differences bring a positive appearance towards happiness and prosperity. Instead, differences become classic problems that create complications based on race, religion and ethnicity which create disharmony. The conclusion is that pluralism cannot be eliminated, but how humans respond to differences in terms of ethnicity, culture, ethnicity and religion so that they can be implemented in the management of Islamic education is seen from the multicultural urgency at SMA As-Salam Bandung. Indonesia merupakan sebuah negara yang mempunyai keragaman, budaya, suku, etnik, bahasa dan agama, dampak dari perbedaan dimasyarat sering terjadi menimbulkan permasalahan dan permusuhan bahkan petumpahan dara akibat heterogen pemahanan. padahal apabila perbedaan dikelola dengan baik akan menghasilkan keragaman dan kesadara bahwa ini semua merupakan anugerah Tuhan yang telah memberikan potensi untuk manjadi masyarakat majemuk dari segi dimensi kultular yang membawa peradaban yang lebih dewasa menuju bangsa yang adil, harmonis, maju dan makmur. Tujuan Penelitian ini untuk mengimplementasikan pendidikan multikultural di SMA As-Salam dalam pendidikan manajemen pendidikan Islam. Metode yang digunakan metode kualitatif dengan pendekatan studi perpusakaan yang selanjutnya dianalisis. Hasil dari penelitian ini, Pendidikan Multikutural sebuah konsep yang harus diimplementasikan dalam kehidupan sehari-hari, khususnya diterapkan disekolah-sekolah agar siswa paradigma/ mainsent atau pola berpikir menerima perbedaan dan saling menghormati, toleransi, kebergaman, persaman hak dan kewajiban berfalsafah pancasila dengan bingkai bineka Tunggal Ika meskipun berbeda-beda tetapi kita satu kesatuan Indonesia. Perbedaan karena hakikatnya hidup segala sesuatu tidak harus sama tetapi bagaimana perbedaan ini dapat membawa nampak yang positif menuju kebahagian dan kemakmuran. Alih-alih perbedaan dijadiakan permasalahan yang klasik yang membuat komplik yang dilatarbelakangi suku, agama dan etnik yang membuat tidak harmonis. Simpulan bahwa kemajemukan tidak bisa dihilangkan tetapi bagaimana cara manusia menyikapi perbedaan dari segi suku, budaya, etnik dan agama agar dapat diimplementasikan dalam manajemen pendidikan Islam dilihat dari urgensi multikultural di SMA As-Salam Bandung.